THE LEVEL OF KNOWLEDGE AMONG UNDERGRADUATE MEDICAL STUDENTS ABOUT STROKE - Rita Arsika Fauziah; Lisda Amalia; Nandina Oktavia; Lulu Eva Rakhmilla (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Stroke is a neurological emergency that requires prompt and precise diagnosis and treatment. However, errors in diagnosis and treatment are still frequently seen. One of the main causes of this problem is the lack of doctors’ knowledge. This study aims to determine the level of knowledge among undergraduate medical students about stroke. The results of this study can be used as basic information to provide educational interventions to medical students to prevent and minimize the occurrence of medical errors. Methods: This study used a quantitative-descriptive method with a cross-sectional approach. The study subjects were third-semester medical undergraduate students at the Medical Faculty of Padjadjaran University during the 2018/2019 academic year. Samples were 43 secondary data collected from ischemic and hemorrhagic stroke Students Objective Oral Case Analysis (SOOCA) exam scores and 168 primary data collected using a 30-item questionnaire regarding stroke knowledge. The data obtained was then analyzed descriptively and the result was categorized into 3 levels of knowledge: Good, moderate, and poor. Results: Each variable demonstrates a varying degree of knowledge. However, based on the total scores and averages collected from both the questionnaire and the SOOCA exam, most of the students had a moderate level of knowledge regarding ischemic and hemorrhagic stroke. Conclusion: Most of the students had a moderate level of knowledge about stroke, so educational interventions and student’s capabilities improvement are required to increase knowledge of stroke.